Hubungan Faktor Individu dan Organisasi terhadap Kepatuhan Bidan Menerapkan Standar Prosedur Operasional Cuci Tangan - Ririk Harlinisari (Universitas Airlangga, 2018)
Background: Infection cases are the major cause of the high rate of morbidity and mortality in the world. Nosocomial infections cause 1.4 million deaths every day in the world. Even the number of nosocomial infections in Indonesia also increases. Therefore, prevention is very necessary to be done. One effective prevention is hand-washing. However, health staffs including midwives still had under 50% compliance to apply Standard Operating Procedure of hand-washing.Aims: The aim of this research was to analyze the influence of individual factors (motivation, knowledge, and attitude) and organizational factors (training, availability of facilities, supervision) on midwives' compliance in applying Standard Operating Procedure of hand-washing.Method: The research was conducted at RSU Bakti Mulia, Banyuwangi. This was an observational research with an analytical and cross-sectional design. The population of the research was 40 midwives in the midwifery unit. The sample size was thirty-three midwives in the midwifery unit determined by Lemeshow formula withm simple random sampling. Data were collected by observation and questionnaire.Results: The results showed that all variables had p values (0,001) < α (0.05). Individual and organizational factors have a significant and positive effect on midwives' compliance in the Standard Operating Procedure of hand-washing.Conclusion: It can be concluded that the higher individual factors (motivation, knowledge, attitude) and the better organizational factors (training, availability of facilities, supervision) are, the higher midwives' compliance in Standard Operating Procedure of hand washing is. However, these factors were still low at RSU Bakti Mulia.Keywords: compliance, hand-washing, individual factor, organizational factor, Standard Operating Procedure